Maternal Stress during Pregnancy and Early Childhood Development - Matias Berthelon; Diana Kruger; Rafael Sánchez (Institute of Labor Economics (IZA), 2018)
There is a consensus in the literature on the relevance of the first 1,000 days since conception in the development of a child's cognitive and non-cognitive skills. However, little is known of the determinants of these skills at that age, as previous literature has focused on the effect of in utero and early childhood shocks on outcomes at birth or at age 7 and beyond. In this paper, we analyze the impact of prenatal stress on cognitive and non-cognitive development of the child by age 2. By exploiting a longitudinal dataset of children and their parents, we find that children who were exposed in-utero to maternal stress do not have different birth-weight relative to those who were not exposed, yet by age 2, exposed children had a lower level of development, cognition skills, and more attention problems relative to children not exposed to in utero stress. We also find that the negative impacts are observed if in-utero stress occurs during the first trimester of pregnancy. The negative impact on cognitive skills and development is concentrated on lower-income children and attention problems occur among high-income children, and boys suffer lower development and worse attention problems, while girls' cognition is negatively affected by in-utero stress.
Keywords: I10; I19; J13; 330; in-utero; stress; early childhood development; maternal stress; maternal mental health; earthquake; Chile